The Association Between Smoking on Olfactory Dysfunction in 3, 900 Patients With Olfactory Loss. (25th February 2020) - Fjaeldstad, Alexander W.; Ovesen, Therese; Hummel, Thomas
Abstract : Objectives/Hypothesis: The association between smoking and olfactory loss remains a conundrum. Prior studies have found negative and positive effects of smoking on olfactory function in the general population. However, smoking cessation seems to improve both rated and measured olfactory function. The purpose of this study was to investigate the olfactory function and smoking habits in patients with olfactory loss caused by different etiologies to unveil underlying patterns related to smoking. Study Design: Retrospective observational study. Methods: Patients were included from two specialized taste and smell centers. Patients underwent olfactory testing, clinical examination including rhinoscopy, and the underlying etiology was identified. Patterns of olfactory test scores, demographics, and etiologies were analyzed. Results: In total, 3, 900 patients with olfactory loss were included. Of these, 521 were current smokers, and 316 were former smokers. Patients with a history of smoking did not have significantly lower olfactory function. Current smokers were more often affected by posttraumatic olfactory loss, but not sinonasal, postviral, or idiopathic olfactory loss. Conclusions: Current smoking, but not former smoking, was associated with posttraumatic olfactory loss. In relation to measured olfactory function, a history of smoking was not associated to lower olfactory scores. Our findings suggest that the general recommendations of smoking cessation for patients with olfactory loss are especially relevant for patients with posttraumatic olfactory loss. The nature of this association between current smoking and posttraumatic olfactory loss has yet to be elucidated. Level of Evidence: 2b Laryngoscope, 131:E8–E13, 2021